Conservation of raptors and vultures in Botswana: with a focus on lappet-faced vultures Torgos tracheliotos - Garbett, Rebecca Ann (Department of Biological Sciences, 2019)
Many raptor species are in steep decline across Africa. Botswana is regionally important for many of these species, including vultures, yet information on most raptors in this area is lacking. Along with the rest of the region, Botswana has seen a rise in poisoning incidences which have decimated vulture populations and threaten other scavenging raptor species. As a result, seven out of the nine sub-Saharan species of vulture are now at risk of extinction. The lappet-faced vulture Torgos tracheliotus exists at very low densities in comparison with other African vultures and in 2015 was up-listed to “Endangered” by the IUCN because of its recent rapid decline. Although it is one of the most commonly seen vultures in Botswana and is widespread across the continent, very little is currently known about its ecology. This thesis aims to provide information on how raptors and particularly vultures are faring in Botswana, the possible threats that they face in this region and how we can use ecological information to alleviate these threats by better protecting these species. I repeated transect surveys of raptors in northern Botswana that were first conducted 20 years ago to investigate changes in abundance of raptor species that were included in the original surveys. I used data for 29 raptor species to compare abundance between the two surveys and found that 14 species (48%) had experienced significant declines of between 37% and 97%, and that overall, 18 species had declined by >50%; three of which were vulture species. When I compared the overall trend between the two surveys, I found a 40% decline in total abundance of all raptors. Only three species (all eagles) showed significant increases in abundance, but these were small (6-15%). I then went on to explore changes in abundance inside and outside of protected areas. In contrast to what was anticipated, I found that only two species showed significantly different trends (both eagles). These trends differed, with one species showing larger declines outside of protected areas than inside of them, and the other species increasing outside of protected areas but remaining stable inside of them. The findings suggest that Botswana raptor populations are declining in-line with global raptor populations and that vultures may be equally at risk in Botswana as in other parts of Africa. Protected areas do not appear to act as a buffer for declines for most raptor species, which suggests that drivers of decline are acting in equal measure inside and outside of protected areas. Furthermore, that drivers of decline are indiscriminate of individual species life history and ecological traits, due to declines occurring across a spectrum of species groups. Elevated lead (Pb) levels caused by the ingestion of spent hunting ammunition are of considerable concern to many species of scavenging birds around the world. The importance of Pb for scavenging raptors in Africa however remains under investigated. I therefore explored the association between blood Pb levels (BLLs) of the critically endangered African white-backed vulture Gyps africanus and hunting activity in Botswana. From 566 individuals tested, around 33% had elevated BLLs above those associated with background exposure. Higher BLLs were associated with samples taken inside of the hunting season and from within hunting areas. Additionally, there was a significant interaction between hunting season and areas, with Pb levels declining more steeply between hunting and non-hunting seasons within hunting areas rather than outside of them. Thus, the results are consistent with the suggestion that elevated BLLs in African white-backed vultures are associated with recreational hunting. Pb is known to be highly toxic to scavenging birds and so it is recommended that Pb ammunition in Botswana is phased out as soon as possible to help protect this rapidly declining group of birds. However, a regional ban would be necessary in order to protect vultures from Pb from hunting across their entire range. GPS tracking data from 14 adult lappet-faced vultures Torgos tracheliotos tracked in Botswana from 2012 to 2017 were used to investigate movement ecology. The GPS tags provided information on overall population home range estimates, as well as on home ranges of breeding and non-breeding birds within different breeding seasons. All vultures ranged widely across the region, regularly crossing international borders. The largest minimum convex polygon (100% MCP) range for an individual bird was almost 700 000 km2 . Within the breeding season, 95% and 50% kernel home range estimates (KDE) were significantly different for breeding and non-breeding birds, with home ranges of breeding birds being up to ten times smaller than those of non-breeding birds. Outside of the breeding season, these differences remained but were less striking. Despite large differences in ranging behaviour, use of protected areas (e.g. amount of GPS fixes within protected areas) by breeders and nonbreeders did not differ, either during the breeding season or in the subsequent non-breeding season. However, actual selection of protected and non-protected areas (e.g. use of protected areas according to their availability) did differ for both breeders and non-breeders. This study suggests that conservation strategies need to be different in order to protect different sectors of a population (which I termed ‘full-spectrum’ protection) over different seasons (e.g. ‘fullcycle’ protection). For wide-ranging species, targeted conservation may be the only way to ensure population survival whilst working within practical conservation constraints. The study of breeding and non-breeding populations will assist in designing successful conservation approaches for many species in decline, particularly those that range widely. Because vultures range over vast areas, they are difficult to protect. Using the lappet-faced vulture GPS data, I explored whether Vulture Safe Zones (VSZs) could be useful for vulture conservation in Africa. VSZs are currently being used in Asia to assist the recovery of three Gyps vulture populations that were driven to near extinction due to veterinary drug – diclofenac, in carrion. To explore whether VSZs would work for African vultures I identified areas of highest use by counting GPS fixes of each individual within each 1-degree gridsquare (DGS) within Botswana (total of 59 DGSs), and then using the mean % of use for each DGS to identify the five top scoring DGSs which would form the VSZ (an area of c. 50,000 km2 ). This was performed for three different groups within the population: 1) all individuals, 2) active breeders and 3) non-breeders. On evaluating the differences between the protection of GPS fixes offered by VSZs for each bird group, the best protection was offered by VSZs targeting breeding birds, at around 80% cumulative protection of their total movements in Botswana, as well as a high level of individual protection. VSZs aimed at protecting non-breeders and all individuals, protected 35% less of their movements in Botswana than VSZs for breeders, as well as offering much less individual protection. Thus, VSZs aimed at protecting breeding birds were most effective and could be a viable conservation tool for adult lappet-faced vultures (or similarly wide-ranging) species in Africa. Further investigations using larger sample sizes should be used within the framework provided in this study to evaluate the potential efficacy of VSZs for protecting African vultures. The findings of this study show that raptors in Botswana are in dire need of conservation attention, but that conservation strategies need to be carefully considered and aimed at achieving ‘full-cycle’ and ‘full-spectrum’ protection of populations. To achieve for African vultures and other wide-ranging species, this will likely require approaches most similar to those suggested for migratory species. Additionally, a move towards protecting ‘greater ecosystems’ e.g. managing wider landscapes outside of protected areas is most likely to be a more realistic step toward protecting wide ranging species and declining global biodiversity in the face of rapidly increasing human pressures across the continent.